Determinants of Student Intention to Work in Hometown - Thủy, Nguyễn Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2015)
Abstract: This empirical research tests the effects of personal emotion and perceived environmental conditions on students' intention to return to their hometown to work after graduation inVietnam. With a sample of 182 students from the National Economics University, the result confirms that students' intention of returning to work in hometown is affected by family support, hometown personal love and perceived environmental conditions. The findings recommend several solutions for policy makers in the provinces including (1) strengthening the relationship between students with their hometown; (2) improving the city quality of life and environmental conditions; (3) providing favourable policies for highly qualified labour resources and more job opportunities; and (4) encouraging their city residents to support and pull their family members back in order to attract high quality human resources for economic development. Keywords: Return hometown intention, graduated student (s), city marketing, environment conditions, knowledgeable worker (s).